Determination of protein‐only RNase P interactome in Arabidopsis mitochondria and chloroplasts identifies a complex between PRORP1 and another NYN domain nuclease. (21st August 2019) - Bouchoucha, Ayoub; Waltz, Florent; Bonnard, Géraldine; Arrivé, Mathilde; Hammann, Philippe; Kuhn, Lauriane; Schelcher, Cédric; Zuber, Hélène; Gobert, Anthony; Giegé, Philippe
Summary: The essential type of endonuclease that removes 5′ leader sequences from transfer RNA precursors is called RNase P. While ribonucleoprotein RNase P enzymes containing a ribozyme are found in all domains of life, another type of RNase P called 'PRORP', for 'PROtein‐only RNase P', is composed of protein that occurs only in a wide variety of eukaryotes, in organelles and in the nucleus. Here, to find how PRORP functions integrate with other cell processes, we explored the protein interaction network of PRORP1 in Arabidopsis mitochondria and chloroplasts. Although PRORP proteins function as single subunit enzymes in vitro, we found that PRORP1 occurs in protein complexes and is present in high‐molecular‐weight fractions that contain mitochondrial ribosomes. The analysis of immunoprecipitated protein complexes identified proteins involved in organellar gene expression processes. In particular, direct interaction was established between PRORP1 and MNU2 a mitochondrial nuclease. A specific domain of MNU2 and a conserved signature of PRORP1 were found to be directly accountable for this protein interaction. Altogether, results revealed the existence of an RNA maturation complex in Arabidopsis mitochondria and suggested that PRORP proteins cooperated with other gene expression factors for RNA maturation in vivo . Significance Statement: RNase P is a key enzyme in tRNA maturation that removes the 5′ leader sequences of tRNA precursors. In this study, the interaction network of the protein‐only RNase P enzyme PRORP1 was identified in Arabidopsis mitochondria and chloroplasts. In particular, an RNA maturation complex was characterized. Results provided insights into the integration of PRORP1 functions with other gene expression processes and helped to understand the diversity of RNase P enzymes in evolution.